Implementation of Horspool Algorithm on Book Search Application in Malikussaleh University Library Based on Mobile Android - Gilang Wahyu Ramadhan Gilang; Zara Yunizar; Sujacka Retno (Proceedings of International Conference on Multidisciplinary Engineering (ICOMDEN), 2024)
The development of information technology encourages innovation in library management systems, one of which is an efficient book search system. This thesis examines the application of the Horspool method in library book search applications to improve search speed and accuracy. The Horspool method is a pattern matching algorithm designed to speed up the text search process by utilizing a sliding table, which significantly reduces the number of comparisons required in pattern search. The developed application allows users to search for books based on title, author, or other keywords with fast and relevant results. An evaluation was conducted by comparing the search time between the Horspool method and the traditional search method. The evaluation results show that the Horspool method offers significant performance improvement, with faster search time and high accuracy.